Desenvolvimento de massa alimentícia sem glúten com adição de Spirulina platensis - Peron, Bianca Colombari (2015)
The biomass of Spirulina platensis is a source of protein, vitamins, lipids and biopigment. These nutrients make the growing interest in microalgae, which can be introduced in food, helping in the fight against malnutrition, especially due to the high protein content (60-70%). In food, Spirulina has been used since ancient times, being legalized in many countries as a dietary supplement. People with gluten intolerance or celiac disease require a restricted diet foods, which causes a shortage of nutrients, which can lead to malnutrition. In view of these considerations, this study aimed to develop a gluten-free pasta added Spirulina platensis, and evaluate technological properties of the same. An experimental design was carried out to evaluate the influence of the addition of microalgae (1.0; 3.0; 5.0%) and emulsifier HPCM (hydroxypropyl methylcellulose) (0; 1.0; and 2.0%) on cooking time response, weight gain, loss of soluble solids and texture. Pasta were prepared from rice flour. The results observed for test formulation 2 were the most suitable in relation to mass control, then this was again prepared on substitution of Spirulina biomass of microalgae for protein concentrate. The masses added biomass and protein concentrate were subjected to physical, chemical and instrumental analyzes. The results were evaluated with Statistica 7.0 software assistance. In technological analyzes the pasta control differed significantly (p<0,05) from mass with concentrated and biomass by great time parameters of cooking and mass increase. Already the results of the chemical composition of the sample mass with protein concentrate was significantly (p<0,05) different other samples, in relation amount of protein. Based on the results it is concluded that with increasing concentration of Spirulina was increased amounts of the protein and therefore the nutritional value of pasta.